The Use of Complementary and Alternative Medicine in Health Care - Mehboob, Riffat (Pakistan Journal of Health Sciences, 2023)
It's kind of mysterious how complementary and alternative medicine (CAM) is being used more and more in developed, "established" Western countries. There hasn't been much study or good understanding about it. The National Center for Complementary and Alternative Medicine (NCCAM) defines "complementary and alternative medicine" (CAM) as a collection of various medical and health systems, procedures, and objects that are not currently regarded as corresponding to traditional medicine. Over the past 15 years or so, CAM use has grown significantly, and it is without a dispute significant from a medical, economic, and sociological perspective. Even though there are literally hundreds of therapies that fall under the broad definition of CAM, only about 15-20 have definitive proof of their efficacy and safety to be taken seriously (Tiran, 2001). The NCCAM divides complementary and alternative medicine (CAM) into five primary categories: whole medical systems, mind-body healthcare, physiologically based, manipulative and body-based therapies, and energy fields [1]. CAM is frequently used to supplement conventional treatment. Back issues, melancholy, sleeplessness, intense headaches or migraines, stomach or intestinal diseases, and back problems were the most frequent symptoms linked with CAM, according to a review of the worldwide CAM literature by Frass et al. [2]. A few earlier studies looked into the use of CAM for particular diseases or health issues, like cancer and multiple sclerosis. According to Menniti-Ippolito et al., herbal medicine was more frequently used to enhance life expectancy while acupuncture and manipulative treatments were mainly used to treat pain in Italy. Homeopathy, in comparison, was not linked to any particular health issues [3]. Other common reasons people turn to complementary and alternative medicine (CAM) are dissatisfaction with biomedicine, frustration with the doctor-patient relationship, relaxation, enhancements in subjective wellbeing, preventative medicine, a preference for natural care over biomedical medicine, and an eagerness for more individualized and holistic care. People in Pakistan who believe in quacks, pastors, hakeems, homoeopaths, or other psychic healers have used alternative treatments. For issues like infertility, seizures, psychosomatic issues, melancholy, and many other illnesses, these are the first line of defense. The proximity, reasonable cost, accessibility, family obligation, and the positive perception of the community are the primary justifications for visiting a CAM healer. Pakistan has a long history of using medicinal herbs to cure a variety of illnesses. The people's health-seeking behavior, particularly in emerging nations, necessitates integrating all CAM healers into society by giving them access to appropriate training, tools, and referral support.